Time Course of Changes in Serum Oxidative Stress Markers to Predict Outcomes for Surgical Treatment of Lumbar Degenerative Disorders. (24th December 2020) - Takahashi, Hiroshi; Aoki, Yasuchika; Saito, Junya; Nakajima, Arata; Sonobe, Masato; Akatsu, Yorikazu; Taniguchi, Shinji; Yamada, Manabu; Koyama, Keita; Akiyama, Yuki; Shiga, Yasuhiro; Inage, Kazuhide; et al.
Abstract : Recent reports indicate that oxidative stress is involved in the pathobiology of acute spinal cord injury or compression myelopathy. We conducted an observational study to determine levels of oxidative stress markers in serum from 80 patients who underwent spinal surgery to treat neurological symptoms related to lumbar degenerative disorders. Serum samples were collected before surgery and at 3 months, 6 months, and 1 year after surgery. Derivatives of reactive oxygen metabolites (ROM) in the serum samples were measured to gauge the level of oxidative stress. For preoperative neurological evaluation, patients were assessed for motor weakness in the lower extremities. We divided the patient samples into two groups: ROM decreasing at 1 year after surgery (G group) and ROM increasing at 1 year after surgery (W group). Then, we evaluated clinical outcomes using the visual analog scale and Oswestry disability index (ODI). Among the samples from the 80 enrolled patients, mean ROM levels before surgery increased to 388.5 ± 92.0, indicating the presence of moderate oxidative stress. The level of ROM gradually decreased after surgery and 1 year after surgery: the levels had significantly decreased to 367.6 ± 83.3 (p < 0.05 ). In patients who exhibited motor weakness, ROM values were significantly increased compared to those patients who had no motor weakness (p < 0.05 ). In analyses of clinical outcomes, ODI values for the W group 1 year after surgery were significantly higher than those for the G group (p < 0.05 ). Moderate oxidative stress was present in patients who had lumbar degenerative disorders and the degree of oxidative stress gradually improved within 1 year after surgery. The clinical results suggest that neurogenic oxidative stress can be mitigated by surgery for patients with lumbar degenerative disorders, and residual oxidative stress reflects poor surgical outcomes.